2021
DOI: 10.1590/0034-7167-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in the COVID-19 pandemic: prevalence and associated factors at a nursing college

Abstract: Objective: to analyze the prevalence and factors associated with psychological distress in students and workers at a public nursing college during the COVID-19 pandemic. Methods: this is a cross-sectional study, carried out by a structured survey based on the internet with a sample of 477 students and workers. Prevalence ratios were calculated and adjusted Prevalence Ratios were obtained by Poisson Regression, with robust variance control and stepwise backward technique. Results: the prevalence of psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
3
7
0
2
Order By: Relevance
“…Similar to our findings, previous research has shown the increased risk of mental health problems among university students with low social support during the new coronavirus pandemic [44,[48][49][50]. Feelings of loneliness and poor perception of family environment resulted in psychological distress during the pandemic [49].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our findings, previous research has shown the increased risk of mental health problems among university students with low social support during the new coronavirus pandemic [44,[48][49][50]. Feelings of loneliness and poor perception of family environment resulted in psychological distress during the pandemic [49].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our findings, previous research has shown the increased risk of mental health problems among university students with low social support during the new coronavirus pandemic [44,[48][49][50]. Feelings of loneliness and poor perception of family environment resulted in psychological distress during the pandemic [49]. Living alone, lack of social interaction with relatives and close friends and weak social ties with other students are the main explanations for the harmful effects of low social support on poor mental health [51].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, it is well-known that BSA molecules have an overall negative surface charge [44], and this could be retained after coating on the Zein-NIC NPs. and 7) before the freeze-drying process (1-4) and after dissolving freeze-dried powder samples in water (5)(6)(7)(8). The laser exposure indicated the Tyndall effects shown by stable nano-suspensions.…”
Section: Particle Size Zeta and Surface Morphology Analysesmentioning
confidence: 99%
“…The whole world has been witnessing a devastating pandemic in the form of coronavirus disease 2019 (COVID- 19), caused by the SARS-CoV-2 virus [1][2][3][4][5][6][7][8][9][10][11][12], ever since it was first discovered in China's Wuhan city in 2019 [13][14][15][16][17]. As of 5 July 2021, there were~184 M individuals worldwide contaminated with this lethal viral disease and 3.98 M people dead.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation